Advancing the Pharmaceutical Potential of Bioinorganic Hybrid Lipid‐Based Assemblies. Issue 9 (20th July 2018) - Wang, Junqing; Wang, Angela Zhe; Lv, Peng; Tao, Wei; Liu, Gang
Abstract: Bioinspired lipid assemblies that mimic the elaborate architecture of natural membranes have fascinated researchers for a long time. These lipid assemblies have gone from being just an imperative platform for biophysical research to a pharmaceutical delivery system for biomedical applications. Despite success, these organized nanosystems are often subject to the mechanical instability and limited theranostic capability without adding any inconvenient modifications. To reach their advanced pharmaceutical potential, various bioinorganic hybrid lipid‐based assembles, which provide new opportunities to synergistically complement and improve therapeutic/diagnostic potential of existing lipid‐based nanomedicine with distinct mechanisms containing inorganic embedded surfactants, have recently been developed. Abstract : Reaching the advanced pharmaceutical potential of lipid‐based assemblies with inorganic building units, the hybridization of biological phospholipids with inorganic embedded surfactants results in mechanically more stable and/or enhanced functional biomembrane mimics. These provide new opportunities to synergistically complement and improve the therapeutic and diagnostic potentials of existing lipid‐based nanomedicine with distinct mechanisms.